THE EFFECT OF VITAMIN C AND AEROMONAS VACCINE ON THE IMMUNE RESPONSE AND DISEASE RESISTANCE OF GROUPER (Epinephelus fuscoguttatus) - Ilmiah, -; Triana, St. Hidayah; Tassakka, Asmi Citra Malina A.R.; Rantetondok, Alex; Anshary, Hilal (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2009)
We evaluated the effectiveness of vitamin C and Aeromonas salmonicida vaccine in grouper (Epinephelus fuscoguttatus) for increasing immune responses and protection against A .salmonicida. The vitamin C used was polyethoxylated ascorbic and tocopherol. The vaccine was prepared from formalin-killed cells and concentrated extracellular products of a single isolate A. salmonicida. Bath immersion vitamin C and vaccine trials were conducted for 60 min. Fish used had a mean weight 25 g. Control groupers were injected with tryptic soy broth. The results showed that vitamin C enhanced phagocytic activity in head kidney leucocytes of grouper 7, 14, 28 and 36 days after treatments. A significant different of the antibody titre was found between control fish and the treated fish at 42 days after treatments. In addition, at day 42, Relative Percent Survival (RPS) for control group was 53.3 %, vitamin C-treated group was 80.0 % and vaccinated group was 90.0 %. The results of this study suggest that bath immersion of vitamin C provided an increasing of phagocytic activity (non-specific immune responses), titre antibody (specific immune responses) and protection against A. salmonicida infection in grouper. A. salmonicida vaccine also en-hanced titre antibody and protection against A. salmonicida infection in grouper.